« Le rôle homosexuel » revisité. Entretien avec Mary McIntosh [1981] - Mary McIntosh; Kenneth Plummer; Jeffrey Weeks (Genre, Sexualité et Société)
In this interview, Mary McIntosh returns to the context in which she produced her article "The homosexual role", highlighting its limits and the amendments she thinks it useful to make. She regrets having considered the matter in an essentially masculine dimension without interrogation and states that it is necessary to no longer take heterosexuality for granted and that homosexuality should be studied through the broad ensemblethatconstitutesthe social organization ofsexuality.